Multidimensional impacts of coronavirus pandemic in adolescents in Pakistan: A cross sectional research. - Nazish Imran; Fauzia Naz; Muhammad Imran Sharif; Sumbul Liaqat; Musarrat Riaz; Abida Khawar; Muhammad Waqar Azeem (PLoS ONE)
Background COVID-19 has posed unique challenges for adolescents in different dimensions of their life including education, home and social life, mental and physical health. Whether the impact is positive or negative, its significance on the overall shaping of adolescents' lives cannot be overlooked. The aim of the present study was to explore impacts of the pandemic on the adolescents' everyday lives in Pakistan. Methods Following ethical approval, this cross-sectional study was conducted through September to December, 2020 via an online survey on 842 adolescents with the mean age of 17.14 ± SD 1.48. Socio-demographic data and Epidemic Pandemic Impact Inventory-Adolescent Adaptation (EPII-A) was used to assess the multi-dimensional effects of the pandemic. Results Among the 842 participants, 84% were girls. Education emerged as the most negatively affected Pandemic domain (41.6-64.3%). Most of the adolescents (62.0-65.8%) had reported changes in responsibilities at home including increased time spent in helping family members. Besides, increase in workload of participants and their parents was prominent (41.8% & 47.6%). Social activities were mostly halted for approximately half (41-51%) of the participants. Increased screen time, decreased physical activity and sedentary lifestyle were reported by 52.7%, 46.3% and 40.7% respectively. 22.2-62.4% of the adolescents had a direct experience with quarantine, while 15.7% experienced death of a close friend or relative. Positive changes in their lives were endorsed by 30.5-62.4% respondents. Being male and older adolescents had significant association with negative impact across most domains (p<0.05). Conclusions Results have shown that COVID-19 exert significant multidimensional impacts on the physical, psycho-social, and home related domains of adolescents that are certainly more than what the previous researches has suggested.